Assisted Living and Medication Adherence in Super-aged Patients With Heart Failure in the Japanese Population. Issue 4 (April 2022) - Kawada, Kei; Kubo, Toru; Ishida, Tomoaki; Jobu, Kohei; Morisawa, Shumpei; Hamada, Tomoyuki; Baba, Yuiti; Kawai, Kazuya; Nakaoka, Yoko; Yabe, Toshikazu; Furuno, Takashi; Yamada, Eisuke; et al.
Abstract: Poor adherence to medication in patients with heart failure (HF) is associated with poor clinical outcomes. Although social support has been reported to improve medication adherence in patients with HF, the detailed underlying mechanism of this association is unclear. This study investigated appropriate social support types to ensure medication adherence, as well as patient characteristics that benefit from such social support in patients with HF. This was a retrospective observational study investigating the association of social support with medication adherence in 824 patients with HF who were registered in a prospective multicenter database. First, we analyzed the association between social support types and poor medication adherence leading to hospitalization. An interaction analysis was performed to detect patients' characteristics that benefited most from social support in terms of medical adherence. Fifty patients (6.1%) were hospitalized for poor adherence to medications. Multivariable analysis revealed that not receiving assisted living, which was defined as having supporting individuals at least once a week, was independently associated with poor medication adherence–related hospitalization. An interaction analysis revealed that patients with dementia benefited from assisted living significantly, whereas male patients or current smokers did not. Summarily, assisted living at least once a week was appropriate for improving medication adherence in patients with HF and was particularly effective in patients with dementia. Performed in a super-aging region in Japan, this study may also suggest the relevance of social support in preventing HF exacerbation in other developed countries that will experience an aging society in the near future.